Which patients with asymptomatic carotid stenosis benefit from revascularization?. Issue 1 (February 2017) - Naylor, A. Ross
Abstract : Purpose of review: To summarize why there are polarized opinions regarding the management of patients with asymptomatic carotid disease and whether it is possible to identify patients who might benefit from carotid interventions. Recent findings: Carotid Revascularization Endarterectomy Versus Stenting Trial and Asymptomatic Carotid Trial 1 (ACT-1) recently concluded that outcomes after carotid endarterectomy and carotid stenting were not significantly different in asymptomatic patients and that procedural risks were below the accepted 3% threshold. However, systematic reviews suggest that Carotid Revascularization Endarterectomy Versus Stenting Trial/ACT-1 results may not be generalizable into routine practice. In parallel, meta-analyses suggest that stroke rates on medical therapy may be declining, suggesting that Asymptomatic Carotid Atherosclerosis Study/Asymptomatic Carotid Surgery Trial data, which have underpinned every practice guideline since 1995, are too historical for use in 2017. A recent review has, however, identified a number of clinical/imaging features that may be associated with higher rates of stroke on medical therapy. Summary: The majority of surgeons/interventionists are unlikely to accept radical changes in practice until new randomized trials confirm that the risk of stroke on modern medical therapy is significantly lower than that previously accepted. In the interim, it would be preferable to target interventions into a smaller cohort who present with clinical/imaging features that might render them 'higher risk for stroke' on medical therapy.